2022
DOI: 10.34172/joddd.2022.035
|View full text |Cite
|
Sign up to set email alerts
|

Color stability of aligner materials on exposure to indigenous food products: An in-vitro study

Abstract: Background. In the recent day, there has been an exponential growth in the usage of clear aligners for orthodontic treatment. As with any removable appliance, the compliance of patients to remove it during ingestion of food is, at times, poor. Thus, the stability of the clear aligner to be "clear" becomes questionable. This in-vitro study examined how the clear aligners changed colour on exposure to various indigenous food products used in everyday life. Methods. Aligners from 5 different companies (K Line, Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Furthermore, Venkatasubramanian et al [ 30 ] conducted an in vitro study examining how clear aligners changed color upon exposure to various indigenous food products. The study found that the hue of the aligners noticeably changed when exposed to substances like turmeric, saffron, Kashmiri red chili powder, and coffee at both 12 and 24 h intervals, reinforcing the trend of worsening color stability over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Venkatasubramanian et al [ 30 ] conducted an in vitro study examining how clear aligners changed color upon exposure to various indigenous food products. The study found that the hue of the aligners noticeably changed when exposed to substances like turmeric, saffron, Kashmiri red chili powder, and coffee at both 12 and 24 h intervals, reinforcing the trend of worsening color stability over time.…”
Section: Discussionmentioning
confidence: 99%
“…The color change rating was determined with the help of the National Bureau of Standards (NBS) system to express color differences [29]. The ∆E* value was converted into NBS units with the formula NBS = ∆E* × 0.92 to relate the magnitude of color change to the clinical relevance standard [30]. NBS rating values are as follows: 0.1-0.5, extremely slight change; 0.5-1.5, slight change; 1.5-3.0, perceivable change; 3.0-6.0, marked changes; 6.0-12.0, extremely marked change; and 12.0 or more, change to another color.…”
Section: Color Change Ratingmentioning
confidence: 99%